A method proposal to detect user movement patterns in urban space: The case of Edirne-Kaleiçi* - Ozkok, Mete Korhan; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, 2023)
This study aims to define the factors that affect users' movement preferences and propose a method to identify the movement patterns in urban space. The proposed method was tested on Edirne-Kaleici, which was chosen as the study area. Edirne proves to be an appropriate case given that the spatial construct of the city bears the characteristics and the political-ideological, social, and economic impacts from different periods throughout history. Thus, the effects of socio-economic factors can be observed when movement preferences are identified. In this context, available literature and different perspectives on movement were examined, and the components that affect movement were revealed. As a result of the model constructed with Natural Movement (based on Space Syntax Analysis Method), Directed Movement (based on Urban Network Analysis Method) and other additional components, movement patterns in the urban fabric were determined. Although the choice, integration, and intensity values are high for users according to the physical construct of streets in Kaleici, the movement remains in a very limited area due to the socio-economic structure and one type of intensive land-use type (retail). In addition, as a result of the correlations made with the observation data (pedestrian-vehicle counts, land market values), the consistency of the model was tested, and a positive/high-level relationship was determined. This method approach will contribute to the literature because it will help integrate many different attributes under the concept of movement and make them questionable.
Keywords: Movement Patterns; Movement Capacity; Space Syntax Method; Urban Network Method; Edirne; NATURAL MOVEMENT; ACCESSIBILITY; SYNTAX; CITIES; CITY; EVOLUTION; LOCATION; FLOWS; LOGIC; FORM; Engineering